2017
DOI: 10.1038/srep45244
|View full text |Cite
|
Sign up to set email alerts
|

The cellular protein hnRNP A2/B1 enhances HIV-1 transcription by unfolding LTR promoter G-quadruplexes

Abstract: G-quadruplexes are four-stranded conformations of nucleic acids that act as cellular epigenetic regulators. A dynamic G-quadruplex forming region in the HIV-1 LTR promoter represses HIV-1 transcription when in the folded conformation. This activity is enhanced by nucleolin, which induces and stabilizes the HIV-1 LTR G-quadruplexes. In this work by a combined pull-down/mass spectrometry approach, we consistently found hnRNP A2/B1 as an additional LTR-G-quadruplex interacting protein. Surface plasmon resonance c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
70
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 52 publications
1
70
0
Order By: Relevance
“…Repression of gene transcriptional represents a main mechanism by which HIV-1 latency is maintained (6). Multiply nuclear factors, including hnRNPs, such as hnRNPA2/ B1, hnRNP U, have been shown to modulate the transcription of latently infected HIV-1 (39)(40)(41). We have previously reported that one hnRNP family member, SAFB1 (scaffold attachment factor B), is capable of inhibiting HIV-1 transcription by preventing the recruitment of RNA pol II to HIV-1 LTR (29).…”
Section: Discussionmentioning
confidence: 99%
“…Repression of gene transcriptional represents a main mechanism by which HIV-1 latency is maintained (6). Multiply nuclear factors, including hnRNPs, such as hnRNPA2/ B1, hnRNP U, have been shown to modulate the transcription of latently infected HIV-1 (39)(40)(41). We have previously reported that one hnRNP family member, SAFB1 (scaffold attachment factor B), is capable of inhibiting HIV-1 transcription by preventing the recruitment of RNA pol II to HIV-1 LTR (29).…”
Section: Discussionmentioning
confidence: 99%
“…A G4 was also detected in hepatitis B virus (HBV) genome, the only member of dsDNA viruses with RT activity [27]. Finally, functionally significant G4s were identified both in the RNA and DNA proviral genome of the human immunodeficiency virus (HIV), a retrovirus belonging to group 6 ( Table 1) [28][29][30][31][32][33][34][35], and [33,34]in the LTR region of lentiviruses in general (ssRNA RT) [36]. Given this amount of scattered data, we here aimed at analyzing the presence of PQSs in the genome of all known viruses that can cause infections in humans.…”
mentioning
confidence: 98%
“…The identification of G4s in microbial genomes has opened up new avenues for therapeutics; additional studies on the specificity of G4-binding ligands and their undesired effects may help us to better understand the therapeutic potential of this novel group of antimicrobial agents. Host protein-microbial G4 interaction or the host G4-microbial protein interactions at the molecular interface of the host and microbe during infection are fascinating and merit further investigation [55,56,[66][67][68][69]. It would be interesting to understand if such interactions defend the host or demonstrate yet another mechanism of microbial pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Nucleolin stabilizes the quadruplex and represses the transcriptional activity of the LTR promoter, allowing the virus to enter latency. Interestingly, heterogeneous nuclear ribonucleoprotein A2/B1 (hnRNPA2/B1), a host protein, binds and unfolds the quadruplex in the LTR promoter of HIV-1 provirus, leading to enhanced transcription [69]. Taken together, these results suggest that G4s in virus genomes may interact with host proteins not only to facilitate virus latency but also to revoke viruses from latency.…”
Section: Role In Virus Latencymentioning
confidence: 99%